A nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere and its preparation method and application

By using ultra-thin carbon walled carbon balls with nitrogen and sulfur double-doped and zinc-loaded as the anode current collector of sodium metal batteries, the problems of sodium dendrites growth, volume expansion and side reactions are solved, and the efficient packaging of sodium metal batteries is achieved and Electrochemical performance improvement.

CN117756097BActive Publication Date: 2025-02-21XIAMEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311640073.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2025-02-21
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

Existing sodium metal batteries have malignant growth, volume expansion and side reactions of sodium dendrites, resulting in safety hazards and rapid attenuation of battery capacity.

Method used

Ultrathin carbon walled carbon balls with nitrogen and sulfur double-doped nitrogen and sulfur loaded are used as sodium metal anode current collector, and are prepared through hydrothermal reaction and high-temperature carbonization to form fully enclosed mesoporous stacked radial carbon balls to achieve high-speed propagation of sodium ions. and efficient packaging of sodium metals.

Benefits of technology

Effectively inhibit the growth of sodium dendrites, alleviate volume changes, reduce side reactions, and improve the negative electrode capacity, Coulomb efficiency and cycling performance of sodium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117756097B_ABST
    Figure CN117756097B_ABST
Patent Text Reader

Abstract

A nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere and its preparation method and application, using zinc acetate dihydrate, thiourea, ethylenediamine, deionized water, and dimethylimidazole as raw materials, through the steps of hydrothermal synthesis of wurtzite zinc sulfide nanosphere precursor, carbonization and etching, to obtain radial carbon spheres stacked by fully closed mesopores. The internal mesopores of the carbon sphere are dense and connected, and the carbon wall is ultra-thin, only at the atomic level. The method provided by the present invention has a reference value for the regulation of zinc sulfide nanostructures, and when the ultra-thin carbon-walled carbon spheres synthesized based on this are used as negative electrode materials for sodium metal batteries, the ultra-thin carbon wall is conducive to the rapid penetration and transmission of sodium, and can achieve nano-encapsulation of sodium metal, thereby effectively limiting the deposition of sodium metal and inhibiting the generation of sodium dendrites, so that the metal battery has good electrochemical cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium metal battery electrode materials, and in particular to a nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere, and a preparation method and application thereof. Background Art

[0002] Today, lithium resources are increasingly scarce, and the development of lithium batteries is also limited. They can no longer meet the rapidly increasing energy needs of society. Compared with lithium, sodium has the advantages of abundant resources (about 2.74wt%, while lithium is only 0.0017wt%), wide distribution, and low cost. In addition, the sodium metal negative electrode has a higher theoretical specific capacity (1166mAh·g -1 ) and a very low standard potential (-2.714V vs standard hydrogen electrode). As a result, sodium metal batteries have gradually come into the public eye and have been widely studied.

[0003] However, when pure sodium metal is used as the negative electrode material, it will cause three major problems: the volume expansion during the deposition of sodium metal will destroy the battery structure and cause battery failure; the malignant growth of sodium dendrites will pierce the battery separator during the charge and discharge process, causing safety problems such as short circuit, fire, and explosion; the unstable solid electrolyte interface film will lead to a large number of side reactions, and the dendrites will break during the cycle to form "dead sodium", resulting in rapid loss of active materials and rapid decay of battery capacity. These key issues that limit the commercialization of sodium metal batteries need to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to solve the above problems in the prior art, and to provide a nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon wall carbon sphere and its preparation method and application, wherein the carbon sphere is a radial carbon sphere formed by stacking fully enclosed mesopores. The mesopores are dense and connected, and the carbon wall is thin, and the structure is only at the atomic level (two layers). When used as a sodium metal anode current collector, high-speed propagation of sodium ions and efficient encapsulation of sodium metal can be achieved, thereby effectively inhibiting the growth of sodium dendrites, alleviating volume changes, reducing side reactions, and thereby improving the negative electrode capacity, coulomb efficiency and cycle performance of sodium metal batteries.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] A method for preparing nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon spheres comprises the following steps:

[0007] 1) mixing zinc acetate dihydrate, thiourea, ethylenediamine and deionized water, and performing a hydrothermal reaction to obtain a zinc sulfide nanosphere precursor;

[0008] 2) grinding the zinc sulfide nanosphere precursor obtained in step 1) with dimethylimidazole, and then in-situ high-temperature carbonization, and finally etching the product with hydrochloric acid to remove the zinc sulfide template, and finally obtaining nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon spheres.

[0009] In step 1), the hydrothermal reaction temperature is 140-180° C., and the hydrothermal reaction time is 14-20 h.

[0010] In step 1), the molar ratio of zinc acetate dihydrate to thiourea is 1:(2-12), and the volume ratio of ethylenediamine to deionized water is (8-15):(52-45).

[0011] In step 2), the mass ratio of zinc sulfide nanosphere precursor to dimethylimidazole is 1:(1-3).

[0012] In step 2), the atmosphere of high temperature carbonization is an inert atmosphere, and after annealing at 180-220° C. for 3-5 hours, carbonization is performed at 600-900° C. for 2-4 hours.

[0013] A nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere, which is a radial carbon sphere formed by stacking fully closed mesopores, the mesopores are dense and connected, the diameter of the carbon sphere is 400-1000nm, and the diameter of the mesopore is 5-20nm.

[0014] The specific surface area of ​​the carbon sphere is 400 to 600 m 2 / g, the thickness of the carbon wall is 0.5~2nm.

[0015] The total doping amount of nitrogen atoms and oxygen atoms in the carbon spheres is 15 wt % to 25 wt %.

[0016] The application of the nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere is used to deposit sodium metal. The sodium metal can be quickly deposited into the cavity in the carbon sphere to form a stable composite sodium metal negative electrode, which is then assembled with sodium vanadium phosphate into a sodium-free full battery with excellent electrochemical performance.

[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0018] 1. The carbon spheres in the present invention have ultra-thin carbon walls of only 0.5 to 2 nm. This structure is extremely conducive to ion penetration and transmission, allowing Na ions to quickly pass through the carbon wall with low transmission resistance and low diffusion barrier, thereby achieving rapid transmission dynamics. Therefore, sodium can nucleate and grow inside the carbon sphere until it completely fills the entire inner cavity;

[0019] 2. The carbon spheres with ultra-thin carbon walls provided by the present invention have a high specific surface area (400-600m 2 / g), with obvious mesopores in the pore size distribution of 5 to 20 nm, which can serve as a stable interface film, thereby reducing side reactions, and can reduce local current density, effectively inhibiting the generation of sodium dendrites;

[0020] 3. The total doping amount of nitrogen and oxygen atoms in the carbon sphere with ultra-thin carbon wall provided by the present invention is 15wt% to 25wt%, and zinc is loaded in the form of single atoms, which can significantly improve the sodium affinity of the carbon sphere and reduce the nucleation overpotential of sodium metal. In addition, the presence of sulfur atoms can simultaneously promote the intercalation and adsorption reactions of ions, further reducing the nucleation barrier of sodium metal;

[0021] 4. The ultra-thin carbon-walled carbon spheres provided by the present invention are stacked by tightly connected fully enclosed mesopores. This structure can not only realize the efficient transmission of sodium ions, but also has relatively good mechanical properties, and can effectively limit the volume change during the sodium deposition / stripping process in multiple cycles of the battery to prevent dendrite puncture;

[0022] 5. In the present invention, under low voltage driving, sodium metal can be rapidly deposited into the carbon spheres by electric driving and capillary action. The entire carbon sphere filling process is usually completed within 40 seconds, showing extremely high sodium affinity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of the wurtzite zinc sulfide nanosphere precursor prepared in Example 1;

[0024] Figure 2 The scanning electron microscope and transmission electron microscope images of the carbon spheres with ultra-thin carbon walls prepared in Example 1;

[0025] Figure 3 The X-ray photoelectron spectroscopy (XPS) graph, nitrogen adsorption-desorption curve and pore size distribution graph of the carbon spheres with ultrathin carbon walls prepared in Example 1;

[0026] Figure 4 Aberration-corrected high-angle annular dark field STEM (HAADF-STEM) image and energy dispersive X-ray spectroscopy (EDS) image of the carbon spheres with ultrathin carbon walls prepared in Example 1;

[0027] Figure 5 This is an in-situ electron microscope experimental picture of the carbon spheres with ultra-thin carbon walls prepared in Example 1 as the sodium metal negative electrode;

[0028] Figure 6 The coulombic efficiency test diagram of the carbon spheres with ultra-thin carbon walls prepared in Example 1 and sodium metal when prepared into a half-cell and the time-voltage cycle diagram when prepared into a symmetrical battery;

[0029] Figure 7This is an electrochemical performance diagram of a full battery prepared with ultra-thin carbon-walled carbon spheres and sodium vanadium phosphate positive electrode prepared in Example 1;

[0030] Figure 8 This is a transmission electron microscopy image of the carbon sphere with a core-shell structure prepared in Comparative Example 1;

[0031] Fig. 9 This is a transmission electron microscope image of the thickened carbon-walled carbon sphere prepared in Comparative Example 2;

[0032] Fig.10 This is an in-situ electron microscope experimental picture of the thickened carbon-walled carbon spheres prepared in Comparative Example 2 as sodium metal negative electrode. DETAILED DESCRIPTION

[0033] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0034] Example 1

[0035] This example is used to illustrate the preparation method of carbon spheres with ultra-thin carbon walls provided by the present invention, which is as follows:

[0036] S1. Add 1.756 g zinc acetate dihydrate into a 100 mL reactor, then add 50 mL deionized water and stir magnetically for 5 min, add 10 mL ethylenediamine, and after another 5 min, add 3.654 g thiourea, and stir the mixed solution at room temperature for 15 min.

[0037] S2. After the above liquid is stirred, the liquid is subjected to hydrothermal reaction at 150° C. for 20 h. After the liquid is cooled to room temperature, the sample is centrifuged and then the obtained solid is washed by centrifugation three times with deionized water / deionized water / ethanol. The sample is collected and dried in an oven at 60° C. for 12 h to obtain a wurtzite zinc sulfide nanosphere precursor.

[0038] S3, take the zinc ore zinc sulfide nanosphere precursor and dimethyl imidazole (mass ratio of 1:2) and grind them together for 10 minutes, then put them into a quartz boat, place them in the middle of the tube furnace, use Ar as the inert gas source, heat up to 220°C at a heating rate of 5°C / h, and keep them warm for 4h, then heat up to 800°C at the same heating rate, and keep them warm for 2h. After the reaction is completed, cool to room temperature to obtain a high-temperature calcined product, collect the high-temperature calcined product and dissolve it in a hydrochloric acid (HCl) solution with a concentration of 6mol / L, stir magnetically to react for 12h, centrifuge, and then wash the obtained solid by three centrifugations of deionized water / deionized water / ethanol, and finally dry it to obtain ultrathin carbon wall carbon spheres, recorded as UtCNS (Ultrathin-walled Carbon Nanospheres).

[0039] The morphology characterization results of the wurtzite zinc sulfide nanosphere precursor prepared in this example are as follows: Figure 1 In a-b, the precursor is relatively uniform, and each nanosphere is composed of tiny rods, that is, hexagonal wurtzite, see Figure 1 In (c), XRD also indicates the successful synthesis of wurtzite.

[0040] The morphological characterization results of the ultrathin carbon wall carbon spheres UtCNS doped with nitrogen and sulfur and loaded with zinc prepared in this example are shown in FIG. Figure 2 As shown. Among them, Figure 2 Figure a is a scanning electron microscope (SEM) image of UtCNS, which shows that the carbonized sample is relatively regular spherical with a relatively uniform structure. Figure 2 Figures b to f are transmission electron microscopy (TEM) images of UtCNS, showing that the carbon spheres of UtCNS are stacked by fully enclosed mesopores, which are radial, dense and connected. The diameter of the carbon spheres is 400 to 1000 nm, and the diameter of the fully enclosed mesopores is 5 to 20 nm. Figure 2 In e to f, it can be clearly observed that the ultra-thin carbon wall is at the atomic level, only 0.5 to 2 nm. Figure 2 In the figure e, the carbon-coated zinc sulfide is shown before the UtCNS is etched, which can more intuitively show the thickness of the carbon wall.

[0041] The XPS spectrum of the nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere UtCNS prepared in this example is as follows: Figure 3 As shown in a, it can be seen that the carbon sphere is rich in nitrogen and oxygen elements, with a content of 17.67wt%, and contains 0.84wt% zinc and 1.71wt% sulfur, which can significantly improve the sodium affinity of the carbon sphere and reduce the nucleation overpotential of sodium metal. The nitrogen adsorption and desorption curves and pore size distribution of the ultra-thin carbon wall carbon sphere UtCNS prepared in this example are shown in Figure 3 As shown in (b), the specific surface area of ​​UtCNS is 510m 2 / g, indicating that it has a rich pore structure and a very high specific surface area, and has a significant mesoporous structure, and the mesopore size is concentrated in the range of 14 to 18 nm.

[0042] The HAADF-STEM spectrum of the ultrathin carbon-walled carbon sphere UtCNS doped with nitrogen and sulfur and loaded with zinc prepared in this example is as follows: Figure 4 As shown in a, the well-dispersed zinc atoms appear as bright spots on the carbon shell, while the EDS image is as follows Figure 4 As shown in (b), the existence of C, N, S and Zn elements and their uniform dispersion in the carbon spheres are further confirmed.

[0043] The in-situ electron microscopy experiment of the ultrathin carbon wall carbon spheres UtCNS doped with nitrogen and sulfur and loaded with zinc prepared in this example as a sodium metal negative electrode is shown in FIG. Figure 5 As shown, where a1 、b 1 The initial state is shown below. The Na electrode is attached to the Cu electrode. Due to the short-term exposure to air during the injection process, Na 2 O can be used as a solid electrolyte, and the upper part is UtCNS glued to the Mo electrode, which is connected to the external power supply to form a closed loop. 2 After O makes it firmly contact with UtCNS, an external voltage of 3V is applied, and Na ions are driven to transfer to UtCNS, and deposit as Na metal after receiving electrons in the inner cavity of the carbon ball. Figure 5 Middle 2 、a 3 、a 4 、b 2 、b 3 、b 4 During the deposition process, it can be observed that Na is continuously deposited into the hollow cavity of UtCNS until the entire cavity of the carbon sphere is filled. The whole process is very fast, taking only 32 seconds, indicating that it has an excellent kinetic reaction process.

[0044] The coulombic efficiency performance of the ultra-thin carbon wall carbon spheres UtCNS doped with nitrogen and sulfur and loaded with zinc prepared in this embodiment as the sodium metal negative electrode and the sodium metal half-cell is as follows: Figure 6 As shown in a, the current density and capacity are 10.0 mA cm -2 and 4.0 mA h·cm -2 , UtCNS can still maintain a high Coulombic efficiency after 500 cycles, indicating that the efficient and sufficient encapsulation effect can effectively stabilize the sodium metal, significantly inhibit the growth of dendrites, and avoid the occurrence of side reactions, thereby maintaining stability and high Coulombic efficiency in long cycles. Figure 6 (b) is the time-voltage cycle diagram of the symmetrical battery prepared by UtCNS, where the current density and capacity are up to 12.0 mA cm -2 and 12.0 mA h·cm -2 Moreover, at a higher discharge depth of 81.7%, the battery can cycle for 750 h, indicating that UtCNS as a sodium metal negative electrode greatly improves the cycle performance of sodium metal batteries.

[0045] The ultra-thin carbon wall carbon spheres UtCNS doped with nitrogen and sulfur and loaded with zinc prepared in this example were used as the sodium metal negative electrode and assembled into a full battery with the sodium vanadium phosphate positive electrode. The performance test was Figure 7 It can be seen that when there is no sodium in the negative electrode, the current density is as high as 1.0 mA cm -2 The full battery has a capacity retention rate of 80% after 90 cycles.

[0046] Comparative Example 1

[0047] This example is used to illustrate the preparation method of the core-shell carbon sphere provided by the present invention, which is as follows:

[0048] S1. Add 1.756 g zinc acetate dihydrate into a 100 mL reactor, then add 55 mL deionized water and stir magnetically for 5 min, add 5 mL ethylenediamine, and after another 5 min, add 3.654 g thiourea, and stir the mixed solution at room temperature for 15 min.

[0049] S2. After the above liquid is stirred, the liquid is subjected to hydrothermal reaction at 150° C. for 20 h. After the liquid is cooled to room temperature, the sample is centrifuged and then the obtained solid is washed by centrifugation three times with deionized water / deionized water / ethanol. The sample is collected and dried in an oven at 60° C. for 12 h to obtain a wurtzite zinc sulfide nanosphere precursor.

[0050] S3, take the above-mentioned wurtzite zinc sulfide nanosphere precursor and dimethyl imidazole (mass ratio of 1:2) and grind them together for 10 minutes, then put them into a quartz boat, place them in the middle of the tube furnace, use Ar as the inert gas source, heat up to 220°C at a heating rate of 5°C / h, and keep them warm for 4h, then heat up to 800°C at the same heating rate, and keep them warm for 2h. After the reaction is completed, cool to room temperature to obtain a high-temperature calcined product, collect the high-temperature calcined product and dissolve it in a hydrochloric acid (HCl) solution with a concentration of 6mol / L, stir the reaction magnetically for 12h, centrifuge, and then wash the obtained solid by centrifugation three times with deionized water / deionized water / ethanol, and finally dry it to obtain a carbon sphere with a core-shell structure, recorded as CsCNS (Core-shell Carbon Nanospheres).

[0051] In the carbon spheres with a core-shell structure prepared in this embodiment, the ratio of ethylenediamine to water is adjusted in step S1 to regulate the structure of the zinc sulfide nanosphere precursor, so that the carbonized carbon spheres present a core-shell structure, and other physical and chemical properties do not change significantly.

[0052] The TEM image of the carbon spheres with core-shell structure prepared in this example is as follows Figure 8 As shown, Figure 8 Figure a shows that CsCNS has a core-shell structure with high and concentrated carbon content inside and a thin carbon layer covering the outside. The diameter of the carbon sphere is 400-1000nm, and the diameter of the carbon core is 280-700nm. Figure 8 In middle b, it can be clearly observed that the distance between the core and the shell of the carbon sphere is about 120 to 300 nm.

[0053] Comparative Example 2

[0054] Also using zinc acetate dihydrate, thiourea, ethylenediamine, deionized water and dimethylimidazole as raw materials, a wurtzite zinc sulfide nanosphere precursor was synthesized by a simple one-step hydrothermal method. Then, the wurtzite zinc sulfide nanosphere precursor and dimethylimidazole (mass ratio of 1:10) were heat-treated and carbonized by adjusting the ratio. After carbonization, etching was performed to synthesize carbon spheres with thickened carbon walls, which were recorded as TwCNS (Thick-walled Carbon Nanospheres).

[0055] Fig. 9 a~c are transmission electron microscopy images of TwCNS. Fig. 9 The transmission high-resolution image of c shows that the carbon wall is significantly thickened, the atomic level is significantly increased, and the thickness reaches 8-10nm. The specific surface area, total nitrogen and oxygen content and spherical size are similar to those in the embodiment. The experimental results show that the carbon sphere cannot achieve nano-encapsulation of sodium metal. Fig.10 As shown, where a 1 、b 1 is the initial state, a 2 、a 3 、a 4 、b 2 、b 3 、b 4 The figure shows that sodium metal gradually sodiumifies the carbon sphere until it is completely sodiumized. Because the number of carbon atom levels in the carbon wall increases significantly, the diffusion barrier of sodium ions increases, and the carbon wall hinders its inward transmission. The diffusion kinetics are very slow, resulting in sodium only filling the interlayers and pores of the carbon wall. The slow diffusion rate leads to the formation of sodium oxide outside the carbon sphere, blocking the channel for the external sodium to further deposit into the internal cavity, showing the phenomenon of only sodiumizing the carbon wall, which will guide the sodium dendrites to nucleate and grow on the outside, resulting in very poor electrochemical performance.

[0056] Since the radius of Na ions is larger ( vs Li ion ), its diffusion energy barrier in the carbon material is high, and the transmission kinetics are relatively slow, which leads to the formation of sodium dendrites. The ultra-thin carbon-walled carbon spheres UtCNS doped with nitrogen and sulfur and loaded with zinc prepared by the present invention not only have extremely high sodium affinity, but also have closed mesopores stacked and supported on each other, and have high mechanical properties. Its extremely thin carbon wall enables UtCNS to realize a "low barrier" sodium transmission and deposition pathway as a sodium metal negative electrode, providing a green channel for efficient sodium encapsulation, thereby effectively inhibiting the growth of sodium dendrites, limiting the volume change during sodium metal deposition / stripping, and stabilizing the interface film, and can be used as an ideal carbon-based current collector material for sodium metal negative electrodes, and then used to construct safe and efficient sodium metal batteries. In addition, the preparation process of the ultra-thin carbon-walled carbon spheres provided by the present invention is simple, and the material cost is low. Carbon spheres with various morphologies can be synthesized by simply regulating the morphology of the precursor, and the wall thickness can also be simply adjusted by changing the carbon source ratio, providing a new idea for the preparation of negative electrode current collector materials for sodium metal batteries.

Claims

1. A method for preparing nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon spheres, characterized in that The following steps are involved: 1) Zinc acetate dihydrate, thiourea, ethylenediamine and deionized water are mixed and subjected to a hydrothermal reaction to obtain a zinc sulfide nanosphere precursor; wherein the volume ratio of ethylenediamine to deionized water is (8-15): (52-45); 2) Grinding the zinc sulfide nanosphere precursor obtained in step 1) with dimethylimidazole, then in-situ high-temperature carbonization, and finally etching the product with hydrochloric acid to remove the zinc sulfide template, thereby finally obtaining nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon spheres; wherein the mass ratio of the zinc sulfide nanosphere precursor to dimethylimidazole is 1: (1~3).

2. The method for preparing a nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere according to claim 1, characterized in that: In step 1), the hydrothermal reaction temperature is 140-180°C, and the hydrothermal reaction time is 14-20 h.

3. The method for preparing a nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere according to claim 1, characterized in that: In step 1), the molar ratio of zinc acetate dihydrate to thiourea is 1: (2-12).

4. The method for preparing a nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere according to claim 1, characterized in that: In step 2), the atmosphere of high temperature carbonization is an inert atmosphere, and after annealing at 180-220°C for 3-5 h, carbonization is performed at 600-900°C for 2-4 h.

5. A nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere, characterized in that: Prepared by the preparation method according to any one of claims 1 to 4.

6. The nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere according to claim 5, characterized in that: It is a radial carbon sphere formed by stacking fully closed mesopores. The mesopores are dense and connected. The diameter of the carbon sphere is 400~1000 nm, and the diameter of the mesopore is 5~20 nm.

7. The nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere according to claim 6, characterized in that: The specific surface area of ​​the carbon sphere is 400-600 m 2 / g, and the thickness of the carbon wall is 0.5~2 nm.

8. The nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere according to claim 6, characterized in that: The total doping amount of nitrogen atoms and oxygen atoms in the carbon spheres is 15 wt % to 25 wt %.

9. The use of a nitrogen-sulfur dual-doped and zinc-loaded ultra-thin carbon-walled carbon sphere according to any one of claims 6 to 8, characterized in that: Used as negative electrode material for sodium metal batteries.

Citation Information

Patent Citations

  • Method for preparing spiauterite ZnS fine nanorod with solvothermal method

    CN102249289A

  • Pomegranate-shaped carbon spheres for packaging zinc oxide nanoparticles as well as preparation method and application of pomegranate-shaped carbon spheres

    CN115924957A